Green Accounting di Daerah Istimewa Yogyakarta: Studi Kasus Antara Kabupaten Sleman dan Kabupaten Bantul - Joko Susilo (Jurnal Akuntansi dan Auditing Indonesia, 2008)
This paper focused on four environmental aspects, environmental awareness, environmental involvement, environmental accounting and environmental audit. Cities have achieved a lot of progress in these fields. Sleman and Bantul are cities that are still in their early stages. The result shows that they are aware of environment protection issues and their commitment to environment protection is high. Their high commitment is represented from their willingness to report and perform environment audit. Unfortunately, what they mean about environmental reporting is qualitative reporting that is absolutely different from environmental accounting. They have not report a quantitative reporting. The result of Mann Whitney test shows that there is difference between Sleman and Bantul in terms of circumstances leading to environmental involvement, environmental reporting, and auditing. Keywords:    green accounting, environmental accounting, sustainability accounting, environmental accounting disclosure